Clothing standards compliance assessment: The modeling and application of clothing standards compliance index. Issue 5 (26th August 2014) - Duncan Kariuki, Ndwiga; Wu, Xiong-Ying; Gao, Chang-Chun; Ding, Xue-Mei
Abstract : Purpose: – Clothing quality, performance, safety and health have become important considerations for consumer welfare. Properties of these aspects are encompassed on standards which regulates clothing products reaching consumers. The purpose of this paper is to categorize these aspects in a common platform by suggesting minimum requirements expected on readymade garments from which clothing standards compliance assessment is performed. Design/methodology/approach: – With the aid of standard compliance assessment model, scored Standard Compliance Rate (SCR) values of the discussed properties of clothing standardization are synthesized from a standard compliance matrix, and the compliance of any clothing standards are assessed and assigned a "Standard Compliance Index/Level (SCI/SCL)" ranging from non compliance to full compliance at six levels. Findings: – In reference to the standard compliance assessment model, 12 children and infant clothing standards, three from Kenya and nine from China, and eight protective clothing standards from Kenya, China, Britain and USA, two from each country, were assessed and the compliance level of each standard evaluated and results presented. The results of the study reveal the importance of every aspect of clothing standardization properties to fulfil the requirements of standard compliance assessment whereby, though they meet their role in developing Standard Compliance Index (SCI), they may have different impact depending with the context applied and the scope of every standard. Research limitations/implications: – The selection of standardization parameters and characteristics, and the criteria for scoring some of the Standard Compliance Rating was subjective and may require mutual agreements between relevant bodies. Furthermore, this method can only be applied on clothing standards and not other textile testing standards. Practical implications: – The proposed method can be applied when evaluating and comparing specific clothing standards between bodies or countries. Clothing SCI would be of primary importance as a guide on required clothing quality specifications to designers, manufacturers, standard regulators and consumer welfare bodies. Originality/value: – This research reports the development of an original framework to assess compliance level of any clothing standard using standardization parameters and characteristics considered when determining the quality of a garment. It establishes a theoretical framework of clothing standards compliance assessment, which has not been reported in the literature to date.